Transformation of the EAEU Tariff Preference System Taking into Account National Interests of the Russian Federation - Evgeniy STEPANOV; Irina KILINA; Yekaterina MALININA; Ksenia POSTAUSHKINA (Communications of International Proceedings, 2020)
The article analyses the use of tariff preference systems in the global economy, explores practical aspects and provides a comparative analysis of existing tariff preference systems in the EU, USA, Canada and the EAEU. The proposed methodology for assessing tariff preferences as an instrument of customs and tariff regulation and the possibility of its flexible use in order to protect national manufacturers. The methodology was tested on the example of the Russian Federation for the period from 2016 to 2019: commodity items were identified in accordance with the FEACN EAEU, for which there is a clear predominance of imports from one or more preferential countries (commodity positions: 2602, 4001, 0202, 0303). An analysis of national production made it possible to single out 0202 and 0303 commodity items of the FEACN EAEU, tariff preferences for which affect the competitive environment for national firms against the general background of the growth of the meat and fish industry in Russia. This situation proves the need for a flexible approach to the use of the system of tariff preferences. Recommendations are proposed on adjusting the current system of tariff preferences of the EAEU taking into account the interests of national producers.
Keywords: International trade; system of tariff preferences; general system of tariff preferences; commodity position; tariff preferences; customs and tariff regulation; EAEU.